Fertilization rate of crossbreeding cattle using sexing and conventional semen in different seasons in South Papua - Nurcholis, Nurcholis; Sumaryanti, Lilik; Irianto, Apri; Salamony, Syetiel Maya (Journal of Advanced Veterinary and Animal Research, 2024)
Objective: Fertilization rate of artificially inseminated cows using sexed and conventional semen in different seasons in South Papua. Materials and Methods: Eighty crossbred cows aged 4–4.5 years with body condition score 3.8 were divided into groups A (summer = 40 cows) and B (rainy season = 40 cows). Each cow in each season was artificial insemination (AI) using sexed frozen semen and conventional semen. Frozen semen was evaluated for post-thawing motility (PTM), cell membrane integrity, and acrosome damage before synchronization using 5 ml PGF2α plus vitamin E. Using a visual gun, we identified cows in estrus on days 4–7 post-synchronization. Pregnancy of cows was detected using N5Vet ultrasound on days 35 and 55. The interaction between season, semen type, and fertilization level was analyzed using standard error and two-way ANOVA, assisted by SPSS 21 software. Results: The wet season Temperature-Humidity Index (THI) level averaged 77.12 ± 1.19, and the summer season THI level averaged 82.67 ± 1.25. PTM quality averaged 60%–65%, viability 61%– 71%, sperm membrane integrity 62%–65%, and acrosome integrity 88%–91%. Conception rates (CR) value of rainy season (p < 0.05) with summer season. In addition, the services per conception (S/C) value in the rainy season (p > 0.05) is the same as in the summer. This study’s S/C and CR values were within normal limits, and the pregnancy rate reached 65%–86%. Pregnancy detection can be observed on day 35, and the fetal heartbeat is visible. Conclusion: Post-AI fertilization using conventional semen was better in all seasons. The double dose of sexed semen can increase the fertilization rate in summer. J. Adv. Vet. Anim. Res., 11(4): 954–960, December 2024 http://doi.org/10.5455/javar.2024.k845